2016
DOI: 10.1128/iai.00285-16
|View full text |Cite
|
Sign up to set email alerts
|

RpiRc Is a Pleiotropic Effector of Virulence Determinant Synthesis and Attenuates Pathogenicity in Staphylococcus aureus

Abstract: fIn Staphylococcus aureus, metabolism is intimately linked with virulence determinant biosynthesis, and several metabolite-responsive regulators have been reported to mediate this linkage. S. aureus possesses at least three members of the RpiR family of transcriptional regulators. Of the three RpiR homologs, RpiRc is a potential regulator of the pentose phosphate pathway, which also regulates RNAIII levels. RNAIII is the regulatory RNA of the agr quorum-sensing system that controls virulence determinant synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 90 publications
(100 reference statements)
2
39
1
Order By: Relevance
“…Sbi is a pro-inflammatory staphylococcal antigen (94) and both forms contribute to S. aureus immune evasion (phagocytosis and Neutrophil killing) (93). In addition to the increased protease and hemolysins production observed, decreased production of Sbi in JE2 Δ rpiRc would suggest increased virulence for this mutant in vivo as previously observed in two in vivo mouse models of abscess and pneumonia using planktonic bacteria (75, 76).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Sbi is a pro-inflammatory staphylococcal antigen (94) and both forms contribute to S. aureus immune evasion (phagocytosis and Neutrophil killing) (93). In addition to the increased protease and hemolysins production observed, decreased production of Sbi in JE2 Δ rpiRc would suggest increased virulence for this mutant in vivo as previously observed in two in vivo mouse models of abscess and pneumonia using planktonic bacteria (75, 76).…”
Section: Discussionsupporting
confidence: 62%
“…They interact together and are all involved in the production or inhibition of extracellular proteins, regulating biofilm matrix stability. A previous publication showed that under planktonic growth conditions, RpiRc positively regulated all these factors (75). The laboratory strain SA113 contains a point mutation in rsbU , the regulator of SigB activity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations